Conceptual framework of Digital Health Public Emergency System: digital twins and multiparadigm simulation - Rodríguez-Aguilar, Román; Marmolejo-Saucedo, Jose-Antonio (EAI Endorsed Transactions on Pervasive Health and Technology, 2020)
INTRODUCTION: Two major technological paradigms have been developed in recent years, digital twins and the multiparadigm simulation. In the Health Sector, the enormous potential of both approaches for the management of public health emergencies is envisioned.OBJECTIVES: This study aims to develop the conceptual framework for the development of a Digital Public Health Emergency System.METHODS: The integration of the digital twins in health with the multi-paradigm simulation for the design of a digital system of public health emergencies is proposed.RESULTS: The proposal establishes the conceptual framework for the integration of a digital public health emergency system, incorporating multi-paradigm simulation in the construction of a digital twin.CONCLUSION: The use of cutting-edge technologies for public health emergencies will allow for a better response to contingencies as well as optimally managing the resources available in a health system.
Keywords: digital twin; multiparadigm simulation; hybrid simulation; health public; pervasive health